Growth accidents induced by primary γ′ precipitates in a polycrystalline nickel-based superalloy. (September 2020) - Charpagne, M.A.; Polonsky, A.T.; Echlin, M.P.; Jacomet, S.; Jaeger, J. de; De Graef, M.; Bozzolo, N.; Pollock, T.M.
Graphical abstract: Abstract: The development of overgrown grains during sub-solvus annealing of a polycrystalline γ − γ ′ nickel-base alloy is investigated, with special emphasis on the primary γ ′ precipitates. Quantitative analysis conducted on a large three-dimensional electron back-scattered diffraction dataset reveals a high fraction of γ ′ precipitates on the annealing twin boundaries in the large grains. When observed in-situ in a scanning electron microscope, the formation of annealing twins is correlated to the crossing of γ ′ precipitates by moving grain boundaries. The role of precipitates in the occurrence of growth accidents is discussed.